The Effect of Global Market Openness on Indonesia’s Tourism Demand - Durrotul Hikmah; Shanty Oktavilia (Universitas Negeri Semarang, 2023)
This study aims to analyze the factors that influence Indonesia’s tourism demand from the Asia Pacific region in 2012-2021. This study uses panel data regression analysis with a random effect model approach. This research is a type of quantitative research using secondary data consisting of cross data, namely cross section data for 8 countries in the Asia Pacific region ana time series data for period 2012 to 2021. The variable used in this study are Indonesia’s tourism demand as the dependent variable and trade openness, per capita income, real exchange rate, and the COVID-19 pandemic in 2020-2021 (dummy) as independent variables. The result showed that the variables of trade openness and income per capita had a positive but insignificant effect on Indonesia’ tourism demand. The real exchange rate variable has a positive and significant effect on Indonesia’s tourism demand. While the dummy is proven to have differences in Indonesia’s tourism demand from the Asia Pacific region before and during the COVID-19 pandemic.